2023
DOI: 10.1001/jamacardio.2023.0494
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cardiovascular Magnetic Resonance Tissue Characterization and Cardiotoxicity in Women With Breast Cancer

Abstract: ImportanceThere is a growing interest in understanding whether cardiovascular magnetic resonance (CMR) myocardial tissue characterization helps identify risk of cancer therapy–related cardiac dysfunction (CTRCD).ObjectiveTo describe changes in CMR tissue biomarkers during breast cancer therapy and their association with CTRCD.Design, Setting, and ParticipantsThis was a prospective, multicenter, cohort study of women with ERBB2 (formerly HER2)–positive breast cancer (stages I-III) who were scheduled to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Our study stems from the hypothesis that early identification and application of radiological patterns can detect anthracycline-induced cardiological damage early and identify patients with occult cardiological disease onset who would benefit from anthracycline-free treatment. Studies which have investigated this topic and have used MRI or CT for the extrapolation of early markers of anthracycline-induced cardiac damage such as ECV and EAT are few in the literature and mainly concern oncology in the context of breast cancer [16,18,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Our study stems from the hypothesis that early identification and application of radiological patterns can detect anthracycline-induced cardiological damage early and identify patients with occult cardiological disease onset who would benefit from anthracycline-free treatment. Studies which have investigated this topic and have used MRI or CT for the extrapolation of early markers of anthracycline-induced cardiac damage such as ECV and EAT are few in the literature and mainly concern oncology in the context of breast cancer [16,18,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that CMR and speckle-tracking echocardiography (STE) are effective diagnostic tools for acute myocarditis [37]. CMR can assess LV volume, LVEF, myocardial strain, early gadolinium enhancement (EGE) to assess hyperemia (inflammation marker), and late gadolinium enhancement (LGE) to assess replacement fibrosis, and it can be used to perform native/post-contrast T1 mapping (with extracellular volume fraction [ECV]) to assess edema and/or fibrosis and T2 mapping to assess edema [38]. LVEF may not be a sensitive indicator for identifying the early risk of cardiomyopathy after radiotherapy, but we know that the disease tends to have a long latency period and requires infinite vigilance.…”
Section: Cardiomyopathymentioning
confidence: 99%
“…Some small-scale studies employing CMR have also demonstrated early myocardial edema following anthracycline therapy using T2w sequences [65]. The presence of edema has been associated with persistent RV function reduction in follow-up examinations [6].…”
Section: Multimodality Imaging Assessment Of the Different Cardiovasc...mentioning
confidence: 99%